Dynamic versus isometric electromechanical delay in non-fatigued and fatigued muscle: A combined electromyographic, mechanomyographic, and force approach - Smith, C. M.; Housh, T. J.; Hill, E. C.; Johnson, G. O.; Schmidt, R. J. (Journal of Electromyography and Kinesiology, 2017)
lThis study used a combined electromyographic, mechanomyographic, and force approach to identify electromechanical delay (EMD) from the onsets of the electromyographic to force signals (EMDE-F), onsets of the electromyographic to mechanomyogrpahic signals (EMDE-M), and onsets of mechanomyographic to force signals (EMDM-F). The purposes of the current study were to examine: (1) the differences in EMDE-F, EMDE-M, and EMDM-F from the vastus lateralis during maximal, voluntary dynamic (1 repetition maximum [1-RM]) and isometric (maximal voluntary isometric contraction [MVIC]) muscle actions; and (2) the effects of fatigue on EMDE-F, EMDM-F, and EMDE-M. Ten men performed pretest and posttest 1-RM and MVIC leg extension muscle actions. The fatiguing workbout consisted of 70% 1-RM dynamic constant external resistance leg extension muscle actions to failure. The results indicated that there were no significant differences between 1-RM and MVIC EMDE-F, EMDE-M, or EMDM-F. There were, however, significant fatigue-induced increases in EMDE-F (94% and 63%), EMDE-M (107%), and EMDM-F (63%) for both the 1-RM and MVIC measurements. Therefore, these findings demonstrated the effects of fatigue on EMD measures and supported comparisons among studies which examined dynamic or isometric EMD measures from the vastus lateralis using a combined electromyographic, mechanomyographic, and force approach.